1x-6-2x+7x=30

Simple and best practice solution for 1x-6-2x+7x=30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x-6-2x+7x=30 equation:


Simplifying
1x + -6 + -2x + 7x = 30

Reorder the terms:
-6 + 1x + -2x + 7x = 30

Combine like terms: 1x + -2x = -1x
-6 + -1x + 7x = 30

Combine like terms: -1x + 7x = 6x
-6 + 6x = 30

Solving
-6 + 6x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 6x = 30 + 6

Combine like terms: -6 + 6 = 0
0 + 6x = 30 + 6
6x = 30 + 6

Combine like terms: 30 + 6 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| 6=4x^2-10x | | 0.64=log(x) | | 3x^2+4x+36=0 | | 36n^2+49=36n | | 3a+8=8a-27 | | 18k=24 | | 2z-8/7=6/7 | | 6a+19=8a-17 | | 74+5x=2x+8 | | v*b*p*z= | | 3b+11=-25 | | 17x-3=10x-24 | | 2x^2+8x-3=13 | | 3x+1/2=2/5 | | 24=8y-3y-1 | | 2s=22 | | 24=8y-3yz-1 | | -8x+56=8x-56 | | z+r+a+k-j= | | -6(-6n-2)-5n=-112 | | 2m+8-4m=12 | | -19z-18=20 | | 400-3x=208 | | 6y-6=2y-3 | | (x+1)(x^2-4x+4)= | | 4t-5=n | | 8x-3=-3+26 | | x^4-34x^2=0 | | |y-3|=2y-10 | | 21=6x+x | | 19y+8+5y=-5y+20+3 | | 3.5=x+.6 |

Equations solver categories